2005
DOI: 10.1002/job.334
|View full text |Cite
|
Sign up to set email alerts
|

Transformational leadership and emotional intelligence: a potential pathway for an increased understanding of interpersonal influence

Abstract: SummaryNon-cognitive emotional intelligence could potentially contribute to a more holistic understanding of interpersonal influence and leadership; however, significant issues of definition, psychometric independence, and measurement must be conclusively resolved. Possible relationships between emotional intelligence, transformational leadership, and individual/organizational outcomes are described and further investigation is encouraged.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
73
0
8

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(90 citation statements)
references
References 8 publications
9
73
0
8
Order By: Relevance
“…The support for a relationship between emotional intelligence and transformational leadership style found in this study serves to advance leadership theory (Brown and Moshavi, 2005), and provides practical applications in leadership development (Nelson et al, 2007). Thus, this study contributes to the knowledge base regarding these relationships by expanding on prior research and potentially paving the way for practical applications in school settings.…”
Section: Purpose Statement and Significance Of The Studysupporting
confidence: 55%
See 2 more Smart Citations
“…The support for a relationship between emotional intelligence and transformational leadership style found in this study serves to advance leadership theory (Brown and Moshavi, 2005), and provides practical applications in leadership development (Nelson et al, 2007). Thus, this study contributes to the knowledge base regarding these relationships by expanding on prior research and potentially paving the way for practical applications in school settings.…”
Section: Purpose Statement and Significance Of The Studysupporting
confidence: 55%
“…However, because a high level of emotional intelligence has been considered a possible antecedent of transformational leadership, further exploration of this relationship was warranted (Brown & Moshavi, 2005). Hallinger's (2003) call for school leaders to employ a transformational leadership style has been supported by empirical research which revealed the principal's impact on school culture or cultural norms (Kelley, Thornton & Daugherty, 2005).…”
Section: James Macgregor Burns' Seminal Publication Of Leadership In mentioning
confidence: 99%
See 1 more Smart Citation
“…These argue over the reality of EI (Antonakis et al, 2009), and how it assessed (Conte, 2005), criticism/advocacy for specific forms of EI (Mayer et al, 2008). Despite this substantial vigilance, affairs of widespread delineation, estimation and the environment of the connection between EI and desired conclusions have not been conclusively settled (Brown and Moshavi, 2005). Recent investigations and reconsiders propose action in the direction of a persistence of long-standing delineation, estimation and submission matters and support the promise worth of EI to organizational behavior (Mayer et al, 2008).…”
Section: Emotional Intelligence (Ei)mentioning
confidence: 99%
“…The trait-based model of emotional intelligence was endorsed by Goleman and Bar-On (Goleman, 1998;Bar-On, 1997); emotional intelligence is defined as a set of non-cognitive attributes, encompassing five broad skill areas: intrapersonal skills, interpersonal skills, adaptability, stress management and general mood (Conte, 2005;Van der Zee and Wabeke, 2004). Previous studies and anecdotal evidence have verified the claim that transformational leadership style could be predicted from trait-based emotional intelligence (Harms and Credé, 2010;Barbuto and Burbach, 2006;Brown and Moshavi, 2005;Mandell and Pherwani, 2003). A number of studies have also been carried out, indicating the ability-based EI to be a determinant of transformational leadership (Daus and Ashkanasy, 2005;Coetzee and Schaap, 2004;Walter and Bruch, 2007).…”
Section: Introductionmentioning
confidence: 98%